Pengaruh Service Excellence (Pelayanan Prima) Dan Tangibless Terhadap Loyalitas Customer Pada Usaha Sablon Kahfi Cloth Di Kota Metro - Romadhoni, Dimas Aldi; Fitriani, Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2021)
One of the efforts made by the company, especially in businesses engaged in clothing services, is to implement quality services that can meet customer satisfaction. The problems that exist in Kahfi Cloth the number of customers tends to decrease. The research design is quantitative research or verification research. The method used in this research is explanatory survey method. The object of this research is service excellence, tangibleness and customer loyalty. This research activity was carried out in the Kahfi Cloth Metro City. The study population with a total sample of 60 respondents. The data collection technique used a questionnaire. The analytical tool used is to use data quality analysis and multiple linear regression analysis with the SPSS program. The results showed partial and tangibles service excellence had a significant effect on customer loyalty. Simultaneously it also shows that excellent and tangibles service together have a significant influence on customer loyalty. Based on the number of coefficients and the value of tcount, it can be seen that the factor that most influences customer loyalty is service excellence.